SQL in a Nutshell, 2nd Edition - Kline, Kevin E. (O'Reilly, 2011)
This essential desktop reference drills down and documents every SQL command and how to use it in both commercial (Oracle, DB2, and Microsoft SQL Server) and open source implementations (PostgreSQL, and MySQL). It includes the command syntax (by vendor, if the syntax differs across implementations), a description, and practical examples. And it also explains how the leading commercial and open sources database product implement SQL. This wealth of information is packed into a succinct, comprehensive, and extraordinarily easy-to-use format.